A STUDY OF SELECTED INDIAN WOMEN’S ENGLISH AUTOBIOGRAPHIES - Khushboo Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The purpose of this chapter is to provide context for the subsequent analysis of the two chosen autobiographies by providing a brief historical overview of the genesis and development of autobiography in Europe and India. In addition to this, it provides a concise analysis of the idea behind autobiography as a literary form. It is remarkable that there is not already a sufficient theory of autobiography written down in the form of books like there is for other types of creative works such as novels, short stories, comedies, one-act plays, and so on. The concept and theoretical study of the autobiographical form, on the other hand, is a meager material presented in a stray and dispersed manner. However, in Dr. M. M. Kanwadkar’s Ph.D. thesis, he made an attempt to gather and arrange such data in order to develop an acceptable theory of the form of autobiography. This was done in an effort to construct an acceptable theory of the form of autobiography. The theory of autobiography that is going to be covered in this chapter adheres very closely to this generally accepted notion. The creative literary skill of autobiography is extremely unique and uncommon. The human need to maintain one’s monument throughout the course of time was the impetus behind its establishment. Autobiography is a very new literary genre, and the name "autobiography" wasn’t used until 1809 when it was published for the first time in the English magazine Quarterly Review by the poet Robert Southey.